Adverse childhood experiences as a risk factor for depression-overweight comorbidity in adolescence and young adulthood. - Kilpi, Fanny; Soares, Ana Goncalves; Howe, Laura D (European Journal of Public Health, 2025)
The comorbidity of depression and overweight is a manifestation of mental-physical multimorbidity, a marker of complex healthcare needs. We sought to examine how adverse childhood experiences (ACEs) are associated with depression-overweight comorbidity in the period of adolescence and early adulthood, and the extent to which associations are sensitive to age, sex, and socioeconomic background. Using data from 4734 adolescents from the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort, we estimated relative risk ratios (RRR) for the associations of multiple ACEs (physical, emotional, and sexual abuse, emotional neglect, being bullied, parental substance abuse, violence between parents, parental criminal conviction, parental separation, parental mental illness, or suicide) with depression only, overweight only or their comorbidity at ages 17 and 24. We tested whether associations differed by sex and socioeconomic background, indicated by parental education. Most ACEs were associated with depression-overweight comorbidity, and there was a dose–response relationship whereby a greater number of ACEs was associated with greater risk, and this continued from adolescence to young adulthood. Some ACEs associations with comorbidity appeared to be influenced by sex: at age 17, females had stronger associations for parental separation and mental health problems, and at age 24, sexual abuse had a stronger association in males. We did not find evidence that the sensitivity to ACEs varied by parental education. ACEs across childhood are associated with depression and depression-overweight comorbidity in late adolescence, which indicates their potential impact on the early manifestation of complex healthcare needs.